Contribution to the fauna of Scarabaeoidea (Coleoptera) of Cres Island, Croatia - Koren, Toni (Annales. Series historia naturalis, 2015)
The first recent overview of the Scarabaeoidea of the Croatian island of Cres is presented. The material for this su-rvey was collected during several field trips organized between 2011 and 2014. A total of 44 species were recorded, 21 of which represent first records for the area. With the records of 10 additional species found in the literature, the number of species known to occur on Cres is 54.
Keywords: Coleoptera; Cres; koprofagni hrošči; pestrost; Scarabaeoidea